Femtosecond laser programmed artificial musculoskeletal systems - Zhuo-Chen Ma (Nature Portfolio, 2020)
Musculoskeletal systems are recognized as a model for designing robust yet flexible microbots but the development of artificial musculoskeletal systems at nanoscale currently remains challenging. Here the authors report a laser programmed artificial musculoskeletal systems for prototyping 3D microbots, using relatively stiff SU-8 as the skeleton and pH-responsive proteins as the smart muscle.